Short-term Effect of Infliximab Is Reflected in the Clot Lysis Profile of Patients with Inflammatory Bowel Disease: A Prospective Study. Issue 3 (March 2015) - Bollen, Lize; Vande Casteele, Niels; Peeters, Miet; Bessonov, Kyrylo; Van Steen, Kristel; Rutgeerts, Paul; Ferrante, Marc; Hoylaerts, Marc F.; Vermeire, Severine; Gils, Ann
Abstract : Background: Inflammatory bowel disease (IBD) is recognized as an independent risk factor for thrombosis. First, we investigate whether the concentration of fibrinolysis inhibitors is increased in patients with IBD. Second, we investigate the effect of infliximab induction therapy on the hemostatic profile. Methods: This prospective study included 103 patients with IBD starting infliximab therapy and 113 healthy controls. Plasma was collected before the first infliximab infusion (wk 0) and after induction therapy (wk 14). Patients not showing a clinical response on induction were considered as primary nonresponders. Fibrinolysis inhibitors were measured by enzyme-linked immunosorbent assay. Using a clot lysis assay, the area under the curve (global marker for coagulation/fibrinolysis), 50% clot lysis time (marker for fibrinolytic capacity), and amplitude (indicator for clot formation) were determined. Results: Patients with IBD selected for infliximab treatment have higher area under the curve (median 29 [interquartile range, 20–38]) and amplitude (0.4 [0.3–0.5]) compared with healthy controls (18 [13–24] and 0.3 [0.2–0.3], respectively, P < 0.001). Primary nonresponders showed a decrease neither in inflammatory markers nor in hemostatic parameters, whereas in primary responders, a decrease in inflammatory markers was associated with a decrease in both area under the curve (29 [20–38] (wk 0) to 20 [14–28] (wk 14), P < 0.001) and amplitude (0.4 [0.3–0.5] (wk 0) to 0.3 [0.3–0.4] (wk 14), P < 0.001). Conclusions: This is the first prospective study demonstrating that the clot lysis profile differs between patients with IBD and healthy individuals. On infliximab induction treatment, this clot lysis profile normalizes in responders suggesting that infliximab treatment is advisable for patients with IBD with an activated hemostatic profile. Abstract : Article first published online 5 February 2015.Supplemental Digital Content is Available in the Text.